2016
DOI: 10.2174/1570159x14666160321122900
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Diabetic Retinopathy

Abstract: Autophagy is an important homeostatic cellular process encompassing a number of consecutive steps indispensable for degrading and recycling cytoplasmic materials. Basically autophagy is an adaptive response that under stressful conditions guarantees the physiological turnover of senescent and impaired organelles and, thus, controls cell fate by various cross-talk signals. Diabetic retinopathy (DR) is a serious microvascular complication of diabetes and accounts for 5% of all blindness. Although, various metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 198 publications
(202 reference statements)
2
83
0
Order By: Relevance
“…Mitophagy is the selective degradation of mitochondria by autophagy and is critical for cells to maintain mitochondrial quality under environmental stress [8], which helps to protect cells from apoptosis and promote cell survival [9]. Recent study showed that DR progression is closely related with mitophagy, which prevents cells from apoptosis and alleviates DR development [10]. In addition, high glucose has been reported to impair autophagy and mitophagy in Neuro-2a cells [11], and induce retinal pericyte apoptosis and death [12], but there are no reports on low glucose’s effects on cell mitophagy and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy is the selective degradation of mitochondria by autophagy and is critical for cells to maintain mitochondrial quality under environmental stress [8], which helps to protect cells from apoptosis and promote cell survival [9]. Recent study showed that DR progression is closely related with mitophagy, which prevents cells from apoptosis and alleviates DR development [10]. In addition, high glucose has been reported to impair autophagy and mitophagy in Neuro-2a cells [11], and induce retinal pericyte apoptosis and death [12], but there are no reports on low glucose’s effects on cell mitophagy and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy consists of non-symptomatic non-proliferative first stage retinopathy, followed by second stage proliferative neovascularization. The proliferative stage consists of extensive angiogenesis of leakage-prone blood vessels [163] driven by HIF1a-induced VEGF. HIF1a may be induced under normoxic conditions by hyperactive mTORC1 [164,165].…”
Section: Non-glycemic Context Of T2d Response To Insulinmentioning
confidence: 99%
“…Autophagy can be involved in a number of degenerative disorders such as Alzheimer's disease (42-46), Parkinson's disease (41, 47, 48), Huntington's disease (49-51), and diabetes mellitus (12, 18, 33, 43, 52, 53). Importantly, autophagy also can impact cognitive decline (12, 54, 55) and aging processes (43, 56-60).…”
Section: Circadian Rhythm and The Modulation Of Autophagymentioning
confidence: 99%